BUDIDAYA DAN PRODUKSI MAKANAN SEHAT DARI KELOR UNTUK MENCEGAH STUNTING DENGAN MEMBERDAYAKAN MASYARAKAT KELURAHAN SONOREJO - Hastuti, Siwi; Pratama, Bangkit Ary; Kustanti, K (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2025)
Stunting incidents currently tend to increase, especially in the Sonorejo sub-district. Stunting can occur due to less than optimal nutritional intake. Stunting can be prevented by processing food from Moringa oleifera L. leaves. No one has cultivated it and does not know the benefits of Moringa leaves for health, especially for preventing stunting. The target of this service is to empower the community in cultivating Moringa plants, producing Moringa leaf-based food preparations and marketing the processed products. The outputs achieved are copyright, scientific publications in accredited journals and mass media publications. Methods for implementing activities include counseling, practice and evaluation. Empowerment was carried out for PKK and Posyandu cadres in Sonorejo Village, parents of stunted toddlers and farmer groups. Counseling takes the form of understanding stunting, how to prevent it by introducing Moringa leaf-based food preparations, and how to cultivate Moringa. Practical activities include making Moringa leaf-based preparations, packaging and marketing methods. Moringa cultivation is done by cuttings and seeds. Evaluation of activities can be concluded that there has been an increase in community knowledge and an increase in community empowerment.